CLUSTER HEADACHE: A NARRATIVE REVIEW OF EPIDEMIOLOGY, DIAGNOSIS CRITERIA, RISK FACTORS, PATHOPHYSIOLOGY AND THERAPEUTIC STRATEGIES - Natalia Wróbel,; Katarzyna Rozkosz,; Katarzyna Torbacka,; Olga Jakubik,; Patrycja Podlejska,; Maja Torbacka,; Zuzanna Wróbel,; Aleksandra Sosin,; Joanna Kaczor,; Wojciech Bednarz, (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Cluster Headache (CH) is a rare but highly disabling primary headache disorder characterized by unilateral pain and cranial autonomic symptoms. It causes major personal and societal burden due to its impact on patients’ quality of life.Purpose of the study: The aim of this review is to provide a comprehensive analysis of CH, including its epidemiology, diagnostic criteria, risk factors, pathophysiology, and treatment. Recent advances in neurobiology and targeted therapies are highlighted.Description of the state of knowledge: Recognized as the most severe of the trigeminal autonomic cephalalgias, CH combines intense head pain with autonomic dysfunction and a distinct circadian pattern. Epidemiological studies report variability in prevalence across regions and demographic groups, with evidence of late-onset and pediatric cases contributing to diagnostic delays.Several risk factors have been identified, including smoking, alcohol consumption, and disturbances in circadian rhythms. Genetic studies reveal susceptibility loci associated with neurovascular regulation, inflammation, and circadian pathways, suggesting a complex genetic background. Functional and structural neuroimaging consistently implicate hypothalamic dysfunction, which interacts with trigeminovascular and parasympathetic systems. Standard treatment includes acute therapies such as subcutaneous triptans and high-flow oxygen, as well as preventive strategies with verapamil.Recent advances have introduced CGRP monoclonal antibodies and neuromodulation, providing new options for refractory patients.Conclusion: Advances in understanding the neurobiological basis and risk factors of CH have enabled more precise diagnostic and therapeutic approaches. However, further research is needed to optimize management and reduce disease burden.